2006
DOI: 10.1172/jci27704
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic pancreas formation in Hes1-knockout mice reveals plasticity of endodermal progenitors of the gut, bile duct, and pancreas

Abstract: Ectopic pancreas is a developmental anomaly occasionally found in humans. Hes1, a main effector of Notch signaling, regulates the fate and differentiation of many cell types during development. To gain insights into the role of the Notch pathway in pancreatic fate determination, we combined the use of Hes1-knockout mice and lineage tracing employing the Cre/loxP system to specifically mark pancreatic precursor cells and their progeny in Ptf1a-cre and Rosa26 reporter mice. We show that inactivation of Hes1 indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
123
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(128 citation statements)
references
References 41 publications
(62 reference statements)
5
123
0
Order By: Relevance
“…The role of HNF1b in early trunk epithelium development, versus differentiation of mature duct cells proper, and if it is similar to HNF6, remains to be determined. It will also be necessary to understand the epistatic and interregulatory relationships between HNF6 and other duct-specific TFs, such as Sox9 (Seymour et al, 2007) and Hes1 (Fukuda et al, 2006) in maintaining proper duct progenitor identity and differentiation programs in the mature pancreas.…”
Section: Exocrine Cell Development Ducts and Centroacinar Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of HNF1b in early trunk epithelium development, versus differentiation of mature duct cells proper, and if it is similar to HNF6, remains to be determined. It will also be necessary to understand the epistatic and interregulatory relationships between HNF6 and other duct-specific TFs, such as Sox9 (Seymour et al, 2007) and Hes1 (Fukuda et al, 2006) in maintaining proper duct progenitor identity and differentiation programs in the mature pancreas.…”
Section: Exocrine Cell Development Ducts and Centroacinar Cellsmentioning
confidence: 99%
“…Indeed, it has even been shown that endocrine clusters, including b-cells, occur naturally in the extrahepatic bile ducts of adult mice (Dutton et al, 2007). The plasticity of the early foregut endoderm is further demonstrated in global Hes1-deficient mice, where significant amounts of ectopic pancreatic tissue containing islets and acini were closely associated with the common bile duct (Sumazaki et al, 2004;Fukuda et al, 2006).…”
Section: Exocrine Cell Development Ducts and Centroacinar Cellsmentioning
confidence: 99%
“…Hes1 maintains progenitors by inhibiting the expression of these bHLH activators. Genetic inactivation of Hes1 up-regulates the expression of these bHLH activators, resulting in, for example, severe pancreatic hypoplasia and the formation of an ectopic pancreas (Fukuda et al, 2006;Jensen et al, 2000;Sumazaki et al, 2004). Hes1 is also expressed in the intestinal crypt, where stem cells and proliferating progenitors are located, and represses the expression of bHLH-type activator genes, Math1 and Ngn3, whose translational products promote the differentiation of secretory cells.…”
Section: Roles Of Hes Factors In Various Tissuesmentioning
confidence: 99%
“…In its absence, foregut endoderm precursors assume an intestinal fate (14). Ptf1a also promotes ectopic pancreas fates from endoderm tissue (16)(17)(18). Mist1 is expressed in a wide array of secretory tissues and, in the adult pancreas, is only detected in acinar cells (19;20).…”
Section: Introductionmentioning
confidence: 99%